2019
DOI: 10.1111/aos.14124
|View full text |Cite
|
Sign up to set email alerts
|

Meibography and corneal volume optical coherence tomography to quantify damage to ocular structures in children with blepharokeratoconjunctivitis

Abstract: Purpose To evaluate non‐contact infrared meibography and anterior segment optical coherence tomography (AS‐OCT) to detect meibomian gland (MG) and corneal changes in children with blepharokeratoconjunctivitis (BKC). Methods We acquired infrared meibography images of upper and lower lids and AS‐OCT corneal scans. One masked observer graded meiboscore, full/partial MG dropout, and measured total corneal volume and differential corneal volume per quadrant and central corneal thickness (CCT). Results We enrolled 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…PBKC is a severe ocular surface inflammatory condition affecting susceptible individuals early in life . Since the report from Viswalingam et al on the clinical relevance of the epidemiology, clinical features, and morbidity of children with Staphylococcal blepharokeratoconjunctivitis, the interest in PBKC has been reflected in increasing publications . The seriousness of the disease lies in its ability to cause considerable vision loss due to corneal damage .…”
Section: Discussionmentioning
confidence: 99%
“…PBKC is a severe ocular surface inflammatory condition affecting susceptible individuals early in life . Since the report from Viswalingam et al on the clinical relevance of the epidemiology, clinical features, and morbidity of children with Staphylococcal blepharokeratoconjunctivitis, the interest in PBKC has been reflected in increasing publications . The seriousness of the disease lies in its ability to cause considerable vision loss due to corneal damage .…”
Section: Discussionmentioning
confidence: 99%
“…6 However, there is evidence that AS-OCT has the potential for use as a diagnostic instrument for dry eye disease in tear film evaluation 8 and meibography. 9,10 The disadvantages of using this equipment are that it is expensive and requires expertise to use. Nevertheless, an advantage of AS-OCT is that it allows for 3D reconstruction as well as the production of 2D infrared images of the meibomian glands.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies found that meibomian gland morphological changes, including meibomian gland atrophy and meibomian gland tortuosity, could begin in children without any symptoms [ 7 , 8 ]. Various ocular and systemic factors have been reported to influence meibomian gland morphology in children, including a higher body mass index (BMI) [ 7 ], blepharokeratoconjunctivitis [ 9 ], digital device usage [ 10 ], and environmental aggravation [ 8 ]. However, the effect of congenital/developmental cataract surgery on meibomian gland function has not been investigated.…”
Section: Introductionmentioning
confidence: 99%